Metastasis suppressor kisspeptin (KISS1) in the blood serum of lung cancer patients - E. S. Gershtein; O. V. Kovaleva; Yu. B. Kuzmin; A. A. Alferov; D. V. Rogozhin; O. O. Yanushevich; I. S. Stilidi; N. E. Kushlinskii (Бюллетень сибирской медицины)
Aim. To conduct a comparative assessment of the content of kisspeptin (KISS1) metastasis suppressor in the blood serum of apparently healthy individuals and patients with lung cancer (LC) and to analyze the associations between the KISS1 level and clinical and pathological characteristics of the disease.Materials and methods. The study included 74 LC patients and 46 apparently healthy individuals. Stage I LC was diagnosed in 8 patients, stage II LC – in 7 patients, stage III LC – in 28 patients, and stage IV LC – in 31 patients. According to the histologic pattern, 32 tumors were characterized as adenocarcinoma, 29 – as squamous-cell carcinoma, 11 – as small-cell LC (SCLC), and 2 – as large-cell lung carcinoma. The pre-treatment KISS1 level in the blood serum was determined using the enzyme-linked immunosorbent assay kit (KISS1, CloudClone Corp., USA).Results. The median serum KISS1 level in LC patients was 213 (range 7.8–716) pg / ml and was significantly higher than in the control group – 83.4 (0–180) pg / ml (p < 0.0001). The ROC analysis of the diagnostic value of serum KISS1 level demonstrated that the sensitivity of the test in relation to the healthy controls was 70% at a cutoff value of 152 pg / ml, and the specificity was 85% (AUC – 0.817; р < 0.0001). In stage I–II LC, the sensitivity did not exceed 50%. The level of KISS1 in the blood serum did not depend on the histologic type of the tumor. No significant differences in the serum KISS1 levels were observed both between non-small cell lung cancer (NSCLC) on the whole and neuroendocrine SCLC and between the main histologic types of NSCLC. The level of KISS1 increased with the disease stage (p < 0.05). However, none of the TNM staging system indices significantly influenced the level of the marker. No differences were found between serum KISS1 levels in patients with central or peripheral localization of the tumor.Conclusion. The KISS1 level was elevated in LC patients compared to healthy controls and was a stage-dependent marker. It has high diagnostic specificity but insufficient sensitivity, especially at early stages of the disease. Based on the results of this study and literature data on the role of KISS1in NSCLC, we conclude that clinical implications of KISS1 in this disease require further research.